THE EFFECTIVENESS OF THE PEGADAIAN DIGITAL SERVICE (PDS) APPLICATION IN IMPROVING CUSTOMER SERVICE AT PT. PEGADAIAN (PERSERO) BIAK BRANCH - Iriawan, Hermanu; Edyanto (Gema Kampus IISIP YAPIS Biak, 2025)
This study aims to determine the effectiveness of the Pegadaian Digital Service application in improving customer service at PT. Pegadaian (Persero) Biak Branch. Biak’s geographical characteristics as an archipelagic area with limited access to conventional services make digital applications a relevant solution to support public services. This research employed a descriptive qualitative method with data collected through interviews, observations, and documentation. Data analysis was conducted interactively throughout the data collection and interpretation stages. The findings indicate that the application has accelerated transaction processes, improved service accessibility, and enhanced internal work efficiency. Customers can now carry out various transactions via mobile devices without the need to visit branch offices. However, challenges remain, particularly for elderly users, residents in areas with poor internet access, and staff members with limited technological proficiency. Nevertheless, there has been a noticeable increase in active users and premium accounts at several service units, reflecting growing trust in this digital service. Overall, the Pegadaian Digital Service application has proven effective in supporting a faster, more independent, and responsive public service transformation. Strengthening digital literacy, developing infrastructure, and enhancing internal training are strategic steps needed to ensure the sustainable implementation of this application.